Role of the cellular immunity in the formation of the immune response in coronavirus infections - I. A. Ivanova; N. D. Omelchenko; A. V. Filippenko; A. A. Trufanova; A. K. Noskov (Медицинская иммунология)
The data obtained during previous epidemics caused by coronaviruses, and current pandemic indicate that assessing the role of certain immune interactions between these viruses and the microorganism is the main pre-requisite for development of diagnostic test systems as well as effective medical drugs and preventive measures. The review summarizes the results of studying patho– and immunogenesis of SARSCoV, MERS-CoV, and SARS-CoV-2 infections. These coronaviruses were proven to suppress development of adaptive immune response at the stage of its induction, affecting the number and functional activity of lymphocytes, effectors of cellular immunity, causing impairment of lymphopoiesis, apoptosis and «depletion» of these cells, thus leading to longer duration of the disease and increased viral load. Information about the role of cellular immunity in development of immune response to coronaviruses is presented. It was proven that the causative agents of SARS, MERS and COVID-19 trigger adaptive immune response in the microorganism according to both humoral and cellular types. Moreover, the synthesis of specific immunoglobulins does not yet point to presence of protective immune response. Activation of the cellular link of immunity is also important. A high degree of antigenic epitope homology in SARS-CoV, MERS-CoV and SARS-CoV-2 is described, thus suggesting an opportunity for cross-immunity to coronaviruses. The review addresses issues related to the terms of specific memory immune cells to SARS-CoV, MERS-CoV and SARS-CoV-2, and their role in providing long-term protection against these infections. Given that specific antibodies to SARS and MERS pathogens persisted for a year, were often not detected or briefly registered in patients with mild and asymptomatic infections, we can talk about important role of the cellular immune response in providing immunity to these coronaviruses. It was shown that, in contrast to antibodies, the antigen-specific memory T cells were registered in patients with SARS virus for 4 to 11 years, and Middle East Respiratory Syndrome – up to two years. Further research is needed to determine presence and number of memory T cells in COVID-19. A comparative analysis of data obtained during previous epidemics with respect to formation of adaptive immunity to coronaviruses. Description of proteins and epitopes recognized by human T lymphocytes will be useful in monitoring immune responses in COVID-19 patients, as well as in developing informative tests to study T cell immune response to SARS-CoV-2 and new preventive drugs.